PENERAPAN MODEL PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN KEMAMPUAN MEMBACA SISWA KELAS I SDN 002 SINTONG KECAMATAN TANAH PUTIH - Nurhasanah Nurhasanah; Lazim N Lazim N; Zulkifli Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : this Research is be executed its low of ability to read student, still many students less ones to know font, achievement consequence study language Indonesia also low. To to overcome it, matter that must be done with to apply it model studying that to intense, student's sehinga active and to motivate student in to know font so to be applied the cooperative studying model with to use it font card. this research Aim to to level it ability read student to through the cooperative studying model-implement. this research Type is class action research (PTK). the Research is done in two cycles each cycle consist on phase planning, action execution, observation and . data collection instrument to research this is teacher's observation sheet and student also test of ability to read. the data that be obtained in this research is ability read student can be seen to student's skor base able ones 4 people whereas less ones able 12 people, with classical completing 25% ( able less). To cycle daily repeating first, the able student 9 people whereas less ones able 7 people, with classical completing 56,25% (able less). To cycle end repeating second to undergo leveling of completing, the able student 14 people, with classical completing 87,50% (able). this research result to be based can to be concluded that the cooperative studying model-implement With To use it Font Card Media can to level it ability to read the I SD class Country 002 SintongKey Word : the Cooperative Studying Model, reading Ability